Ernani Maria Fiori: a Brazilian professor in Chile - testimonies - Lucidio Bianchetti; Carlos Eugenio Beca; Cecilia Richards (Universidade Federal do Rio Grande do Sul, 2013)
This text is a testimonial to professor Ernani Maria Fiori (1914-1985), and highlights his sustained support for the reform of the Catholic Univeristy of Chile, which took place in the 1960s and which marked the personal history of those who participated in it, as well as the political, social and educational history of Chile until today. As Assistant Academic Dean of the university, professor Fiori contributed to shaping the school with his solid intellect and his humanity, as he participated in the educationof a generation of professionals who in some form or another, and despite the impediments established by the military dictatorship, have continued to be his disciples: as is highlighted in this testimonial. Don Ernani Maria Fiori lived in exile in Chile, a situation that did not prevent him from adopting the task of reforming the university with wisdom and kindness, meeting the needs of Chilean society at the time.